The Influence of Social Interaction and Children's Language Ability on Students' Language Politeness in Class IV UPTD SD Negeri 06 Sei Muka, Datuk Tanah Datar District, Batu Bara Regency - Vera Sasmita; Abdurahman Adisaputera; Daulat Saragi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to determine the effect of social interaction and children's language skills on language politeness of fourth grade students at UPTD SD Negeri 06 Sei Muka, Datuk Tanah Datar District, and Batubara Regency. Data collection was carried out by using a questionnaire for social interaction variables and language politeness, and multiple choice tests for language proficiency variables. Data were analyzed using multiple regression analysis techniques. The results of this study show that the Social Interaction variable has a positive influence on Language Politeness. The results of data analysis for the effect of Social Interaction on Language Politeness amounted to 0.000 <0.05 and tcount 27.531> ttable 2.063. Obtaining data for the effect of Language Ability on Language Politeness is 0.024 <0.05 and the tcount value is 2.431> ttable 2.063. Based on the results of the data analysis that has been done, the Language Ability variable affects Language Politeness. While the results of data analysis for the effect of Social Interaction and Language Ability together on Language Politeness is 0.000 <0.05 and the value of Fcount is 349.654> Ftable 3.39, so it can be concluded that the Ha test is accepted, which means that there is an influence of Social Interaction and Language Ability together on Politeness of Language.